Technology mapping of multi-output functions leading to the reduction of dynamic power consumption in FPGAs - Opara, Adam; Kubica, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
This article presents a synthesis strategy aimed at minimizing the dynamic power consumption of combinational circuits mapped in LUT blocks of FPGAs. The implemented circuits represent the mapping of multi-output functions. Properly selected multi-output functions are described using a new form of the binary decision diagram (BDD), which is an extension of pseudomulti-terminal BDDs (PMTBDDs) in the literature. The essence of limiting power consumption is to include additional parameters during decomposition, such as the switching activity associated with the switching PMTBDD (SWPMTBDD).
Keywords: low power synthesis; FPGA; switching activity; decomposition; technology mapping